THE PROBLEM OF THE FATE OF FAMILY AND SOCIETY IN JADID LITERATURE (Scientific journal of the Fergana State University, 2024)
There have always been brilliant artists throughout human history who have dedicated their life, ideas, and inventiveness to making people's lives better now and better tomorrow. Even though a number of nationalist writers were suppressed and erased from our spirituality's history, studying their legacy and the ethical and spiritual questions they highlighted remain relevant in today's independent world. Since the fundamental purpose of their work was to serve as a means of articulating the aspirations of the nation and society and to establish the nation's identity. Individuals exhibiting selflessness include Mahmudhoja Behbudi, Abdulla Qadiri, Abdulhamid Cholpon, and Abdurauf Fitrat. Their acts of selflessness extend beyond their creative endeavors.Every nation is created through a protracted historical development process. Its creation occurs in certain natural socioeconomic environments. A representative of society is formed by the entirety of the web of social relationships, in addition to the freedom of the country to which he belongs, a prosperous family life, and the social and cultural milieu. A person's spiritual image is shaped by these social relationships. The degree to which an artist is spiritually connected to a nation greatly influences their capacity to accurately capture in a work of art that nation's spirit, desire, and national mindset. Based on Abdulla Qadiri's life and work, this article examines the linked features of the familial environment, personality decline, and crises in social and spiritual life.